Effect of superheating temperatures on microstructure and properties of strontium modified aluminium–silicon eutectic alloy - Haque, Md. Mohafizul; Ismail, Ahmad Faris (Elsevier, 2005)
Superheating temperature on strontium modification of Al–Si alloy has tremendous effect on its solidification characteristics, which determines the structural refinement and hence the properties of the alloy. In this study, it is observed that as the superheating temperature is increased up to an optimum temperature of 750 °C, the eutectic silicon becomes more globular and well distributed all over the entire structure. At the same time, the iron rich β needles become thinner and thinner as superheating temperature is increased. The embrittling effect of iron rich phase in the modified alloy also reduces, when it is present in the structure as fine and thin needle. The fractured surfaces show that the strontium modification minimizes the source of stress concentration regions in the cast samples. The melts, superheated to 730 and 740 °C, showed some white regions in the fractured surfaces, but when superheated to 750 °C, the fractured surfaces were free from such accumulation of white phases. The SEM analysis showed that the concentration of strontium on those white regions was more than any other areas of the fractured surfaces. It is believed that some undissolved strontium may appear in those white regions of the cast specimens, especially when melted at low superheating temperatures. At the superheating temperature of 750 °C, all phases were refined and well distributed throughout the entire structure, resulting a higher strength and ductility. Therefore, 750 °C is considered to be the optimum superheating temperature for the purpose of modification of aluminium–silicon eutectic alloy with strontium.